2018
DOI: 10.2214/ajr.17.19023
|View full text |Cite
|
Sign up to set email alerts
|

Screening Mammography Findings From One Standard Projection Only in the Era of Full-Field Digital Mammography and Digital Breast Tomosynthesis

Abstract: One-view-only findings occur with both FFDM and FFDM-DBT and remain an important but uncommon sign of malignancy. They are more frequent, are more likely to represent summation artifacts, and have a lower PPV with FFDM than with FFDM-DBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…Although some studies have shown lower recall and false positives with DBT [6][7][8] , this was not confirmed in the present review. Our analyses did not find evidence for differences in recall rates between DBT (with digital or synthetic mammography) and digital mammography alone.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Although some studies have shown lower recall and false positives with DBT [6][7][8] , this was not confirmed in the present review. Our analyses did not find evidence for differences in recall rates between DBT (with digital or synthetic mammography) and digital mammography alone.…”
Section: Discussioncontrasting
confidence: 90%
“…After completely reading these references, 18 studies (comprising 26 articles, since some had more than one published article) met our eligibility criteria and therefore were included in this review [4][5][6][7][8][24][25][26][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overlying fibroglandular tissue can mask a cancer, decreasing the sensitivity for breast cancer detection particularly for women with dense breasts (1,2). It can also cause summation artifacts, resulting in false-positive findings and more recalls, leading to additional studies and/or procedures (3).…”
Section: Introductionmentioning
confidence: 99%